Evaluación de la extracción de colágeno en piel de bovinos (2020)
Bovine hides are used as raw material in the tanning industry for application in textile industries, however, the preparation of these hides involves a series of polluting products that consecutively affect the environment. Extracting collagen from bovine skin can be considered as an alternative to tanning the leather, in order to generate less waste and guarantee another application for bovine skin. There are different methodologies for obtaining collagen, which by means of a decision matrix and some evaluation items such as efficiency, equipment and reagent costs, time and environmental impact, it was concluded that the best route to obtain collagen was The chemical method, since it showed better qualifications against the proposed evaluation items, is also considered a faster and cheaper method, however the extraction yield obtained in bovine splits according to the literature was 11%